Percepção e riscos de adoecimento dos trabalhadores da indústria frigorífica: uma abordagem psicodinâmica - Schiehl, André Roberto (2012)
This case study was undertaken in a large freezer factory in an inland city in the state of Paraná to evaluate activities carried out in freezer rooms at ambient temperatures of between 10º C and -35º C. The main objectives were: to analyze the work processes in a freezer factory with respect to factors such as working conditions, physical injuries and physical costs; to diagnostically compare factors related to the levels of pleasure and suffering of the workers; and to indicate the key risks inherent in the activities performed. The results were obtained through the use of the ITRA (Inventory on Labor and Risk of Illness) with the participation of 178 employees. The ITRA comprises 4 scales of 13 factors totalling 124 items. These employees were classified into different groups according to level of education, marital status, length of service, shift, age and temperature at which they worked. For statistical analysis the Statistica program, version 5.0 (Statsoft ®) was used. Within the work processes, the following were identified as representing major risks to workers‟ health: working at height, the possible leak of toxic gases, misuse of compressed air and electric shocks, however contains all risk control measures. The most obvious health risks to employees were torsion of the lumbar spine, overloading of the knees and risks from being squeezed, bumped and bruised. In relation to the „working conditions‟ factor, all the items were classified at the „unsatisfactory‟ level, with statistically significant differences in some items related to type of shift and age. Regarding the „physical cost‟ factor, most responses were also rated as „unsatisfactory‟ with some differences related to length of service, working temperature and shift. With reference to the „physical injuries‟ factor, the responses were heterogeneous, with some items on the scale considered to be „severe‟. Statistical difference was observed for education, marital status, length of service and shift. Temperature was not identified as a variable with a negative influence on the work process. In terms of the „shift‟ factor, employees working on night shifts gave worse ratings, indirectly reflecting the emotional and mental stress of working at night. The „length of service‟ factor generally indicated that suffering decreased over the years. Among the items surveyed, only 6% were classified as „severe‟, 61% were „unsatisfactory‟, and 33% were „tolerable‟. No item was classified as an „occupational illness‟. The overall average of the 13 factors analyzed, ranked 10 as „unsatisfactory‟ and 3 as „tolerable‟ or satisfactory.